THE EFFECT OF TRUST AND ELECTRONIC WORD OF MOUTH ON PRODUCT PURCHASING DECISIONS ONLINE - Dede Suleman; Dedi Suharyadi; Rini Martiwi; Nyoman Suardhita; Enggar Widianingrum; Eulin Karlina (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This research aims to examine the effect of trust and electronic word of mouth (eWOM) on product purchasing decisions. Trust is considered a crucial factor in consumer decision-making, and eWOM has emerged as a powerful tool for shaping consumer opinions and attitudes towards products. The study uses a survey questionnaire to collect data from a sample of consumers and employs structural equation modeling (SEM) to analyze the relationships between the variables. The research proposes the following hypotheses: Trust has a positive effect on product purchasing decisions. eWOM has a positive effect on product purchasing decisions.The results of the study provide insights into the role of trust and eWOM in shaping consumer purchasing decisions and highlight the importance of building trust and leveraging eWOM to promote products effectively. The findings of the research can inform marketing strategies and help businesses develop more effective approaches to influence consumer behavior.